Structure-property relationships in framework materials: anomalous mechanics by design - Collings, I; Ines Collings (2014)
Framework materials that contain molecular bridging ligands between metal nodes—as seen in coordination polymers—not only give rise to enhanced structural diversity, but also to a range of useful and unusual mechanical properties. This thesis demonstrates the general structure–property relationships that are developed for coordination polymers in order to enable prediction and design of their mechanical properties, and hence structural flexibility. Variable-temperature and -pressure diffraction experiments are employed for the determination of their mechanical properties, namely by calculating thermal expansion and compressibility coefficients. The anomalous and varied mechanical responses observed are rationalised by the important structural features, or the so-called mechanical building units (XBUs), of the coordination polymers. The XBUs are considered within the setting of framework topology, geometry, and composition in order to establish general design principles for targeting different degrees of flexibility within coordination polymers. The XBUs are identified first in silver(I) 2-methylimidazolate, Ag(mim), a framework which is comprised of structural motifs of varying strength, namely argentophilic interactions, hinge points and metal–ligand bonding. The anomalous mechanical responses in Ag(mim) are shown to be rationalised entirely by the XBUs present in the structure. The XBU abstraction is then applied to a range of other coordination polymers and shown to correspond directly with the anomalous responses known in these materials. The metal–ligand–metal linker XBU is investigated further in both cadmium imidazolate, Cd(im)2, and zinc cyanide, Zn(CN)2. Here, the linker chemistries are completely different between the two frameworks, but the diamondoid arrangement of the linkers, and thus the topology, is the same. The structural responses of the two frameworks are examined to unravel the extent of topology- and chemistry-driven mechanics. It is found that the topology dominates the atomic displacements of both frameworks, indicating the existence of common soft-mode dynamics which are likely to extend to other coordination polymers with the same topology. The three-dimensional framework-hinging XBUs in zinc isonicotinate, Zn(ISN)2, and indium deuterium terephthalate, InD(BDC)2, are considered next. These frameworks have the same topology but contrasting framework geometries, evident from the differing c/a-lattice parameter ratios. In this case, a geometric formalism is derived which can predict the direction of framework mechanical anisotropy in Zn(ISN)2 and InD(BDC)2 and other uniaxial coordination polymers. Finally, a family of ABX3-type transition metal(II) formates are investigated, where both the B-site and A-site cations are varied. The chemical modifications give rise to variations in B- or A-site cation sizes, which are found to correlate with the magnitude of mechanical responses. These structure–mechanical property relationships—based upon framework topology, geometry and composition—are presented in separate chapters, and in each case generalised so that they can be applied to a range of coordination polymers. Hence the design principles determined here can provide the materials science community with an intuition on the type and magnitude of responses possible in these materials under different external stimuli.